Morphological Development in a Bhutanese Child: A Case Study of English as A Second Language Acquisition - Tenzin (Indonesian Scientific Publication, 2026)
This study examines the morphological development of a 58-month-old Bhutanese child, Dorji, learning English as a second language in a multilingual setting. The study employed a qualitative case study design focusing on speech samples collected during spontaneous father–child interactions. Mean Length of Utterance (MLU) and grammatical morpheme analysis were applied to assess linguistic complexity, emphasizing on plural markers, verb inflections, negations, and interrogatives. The findings indicated an MLU of 5.94, which is within the typical range range of first language learners, suggesting advanced morphological competence despite English being the child’s second language. The child demonstrated strong Cognitive Academic Language Proficiency (CALP), which is evident from the use of academic vocabulary such as “gravity” and “helium planet.” However, weaker Basic Interpersonal Communicative Skills (BICS) were observed through limited conversational fluency and inadequate use of negation and question structures.The study indicated the critical role of parents in teaching early morphological development, while limited exposure to spontaneous peer interaction may hinder functional grammar growth. Overgeneralization of morphological rules, inconsistent auxiliary usage, and reliance on rising intonation for questions reflected an early developmental stage in conversational competence. Thus, the study highlighted the importance of balanced language exposure that integrates both structured academic discourse and naturalistic communication. It contributes to the limited body of research on second language acquisition in underrepresented multilingual contexts and offers pedagogical implications for early language instruction, parental involvement, and curriculum design for both academic and communicative language proficiency.